Relationship between blood concentration of zinc and selenium and prognosis in post-acute myocardial infarction: A protocol for systematic review and meta-analysis - Ana Francisca Teixeira Gomes; Lisandra Mikaely Barboza da Silva; Raissa Beatriz Silvestre Carneiro; Raquel Costa Silva Dantas-Komatsu; Gidyenne Christine Bandeira Silva de Medeiros; Vivian Nogueira Silbiger; Bruna Zavarize Reis; André Ducati Luchessi (PLoS ONE, 2025)
Acute Myocardial Infarction (AMI) is characterized by the presence of injury caused by an ischemic event, which leads to various complications, including Heart Failure (HF), the most severe functional stage of the heart, reducing both quality of life and life expectancy. Among the factors involved in this process, essential trace elements such as zinc and selenium stand out, as they are related to cardiovascular health and may help mitigate the harmful changes resulting from AMI. The objective of this protocol is to detail the development of two systematic reviews to gather scientific evidence on the relationship between zinc and selenium and the prognosis following AMI. This protocol was developed in accordance with the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P) guideline and registered in the International Prospective Register of Systematic Reviews (PROSPERO) under the code CRD42024574424. Search strategies will be conducted using a combination of controlled and uncontrolled terms combined with Boolean operators, and the following databases will be used: MEDLINE/PubMed, EMBASE, LILACS, Scopus, Web of Science, Trip database, and World Wide Science. Cohort studies that evaluated zinc and selenium in the prognosis after AMI will be included. Two trained researchers will independently select articles, extract data, and assess the risk of bias and the quality of the evidence. A narrative synthesis will be performed, and the main findings will be presented in tables. If possible, a meta-analysis will also be conducted.